The fatigue strength of bidirectionally bent steel cord used in tyres. (November 2019) - Kruzel, Robert; Ulewicz, Malgorzata
Abstract: The article provides the results of fatigue life testing of steel ropes responsible for carrying longitudinal and transverse loads, used in construction machine tyres. The fatigue life of such a steel rope depends on factors associated with its construction, execution quality, as well as on wire patenting conditions. The fatigue strength of steel ropes under bidirectional bending conditions was compared for different cord constructions and for cords made of different steel grades on a specially designed, innovative testing machine for steel ropes. Moreover, the effect of heat treatment on a patenting line on the properties of cord wires was determined. Graphical abstract: Unlabelled Image Highlights: Cord winding method, diameter and number of wires influence on tension of steel cord. Decrease of steel cord strength is not a linear relationship. Distribution of fatigue cracks in steel cards depends on the number of bends. Modification of standard wire heat treatment parameters improves cord's properties. The lowest steel cord strength was found for the 3 × 0.25 6 × 0.35 construction cord.